Improving water utilization from a catchment perspective - Batchelor, C.; Cain, J.; Farquharson, F.; Roberts, J. (International Water Management Institute, 1998)
The System-Wide Initiative on Water Management (SWIM) has defined its central theme and objective as ?enhancing the productivity of water and agriculture in an environment of growing scarcity and competition.? One program area of SWIM, namely SWIM 7, has the aim of improving the utilization of water resources from the catchment perspective. This paper has been prepared as part of the process of planning research that is to be undertaken by SWIM 7. The paper includes a historical review of research that has involved the use of catchment experiments and a discussion on hydrological modeling techniques. Options for improving water utilization at the catchment and farm scales are identified, and recommendations are made for research that might be undertaken by SWIM 7. The case is argued for interdisciplinary catchment studies that involve the participation of local communities and other stakeholders.